The Hemostatic Defect of Acute and Chronic Uremia - Donner, L; Neuwirtová, R (Thrombosis and Haemostasis, 1961)
1. Investigations of blood coagulation in 52 acute, and 38 chronically uremic patients were performed. Clinical bleeding tendency were noted in 16 (30,8%) patients with acute uremia and in 13 (34,2%) with chronic uremia. In 237 extracorporeal dialysis carried out during the last 4 years, bleeding occurred in 55 (22,3%) during the procedure.2. Both acute and chronic uremia are associated with numerous coagulation disturbances. Single laboratory alterations are not uniformly present in patients with uremia, changes in the thrombelastographic patterns, of the prothrombin and fibrinogen are most frequently found.3. There was a striking tendency for the thrombelastogram to assume particular patterns similar in appearance either to the narrowing of a bottle-neck, a gradual joining, or to an onion like pattern. It is suggested that blood platelets take part in the development of these changes.4. In comparing laboratory changes in acute and chronic uremia there are no significant differences in single laboratory changes. Although factor VII tends to be lower in acute uremia as compared with chronic uremia and the prothrombin consumption test lower in chronic uremia than in acute uremia.